"Na boca da noite, um gosto de sol" : leitura e formação, literatura e ensino, em narrativas de professores de língua portuguesa - Bassani, Geraldo (2014)
This work aims at understanding, through the History of Education in Espírito Santo perspective, the establishment of Literature as a school subject, as well as its teaching strategies, especially the use of literary texts in the classrooms, or in after class activities. It analyses the narratives of teachers of Portuguese Language and Brazilian Literature, within the decades of 1960 and 1980, when the Law 5.692, of 1971, passed. This Law conceived education as an instrument to serve technocratic and developmental rationality. Besides those teachers narratives, it presents documents, letter of the law, official guidelines, academic works and students’ books of that period; basing the analysis on Ginzburg’s propositions (2002,2003,2007), especially the notions of multiplicity of sources and relationship of forces. It understands the data and the narratives production from the analyzed context – the state of exception, which started in 1964. Hence, a narrative of History is consisted (CERTEAU, 2010), dialoging with the relations between past and present (BLOCH, 2001) and with the value of the narrative and the experience elaborated by Benjamin (2012a, 2012b). It considers that the teachers’ reading and academic formation, as well as their insertion in culture and society, have composed not only their ways of teaching, but also their choices among authors and literary works. State of exception, developmentalism, cultural movements, civic pride, moral, as well as educational and social tendencies of that time flash (BENJAMIN, 2012c) in its reminiscences, reconfigured in the present; revealing the forces that were related. Despite the apparent lack of direct intervention in the practices of the narrators, the Literature approach was processed in nets of forces weaved by their own academic, family and social values, as well as ideological values circulating in the investigated period, establishing criteria, which, under this tension, while selecting, also excluded authors and works from the school environment. This thesis moves towards the consideration of contributions, for both men and History, (CALVINO, 1993), that Literature, as a way of reconfiguring the truth (CALVINO, 2012) may bring, and redimensions its mission. (SEVCENKO, 2003).